Potential drug–drug interactions and clinical outcomes among people living with HIV with comorbidities: A multicentre retrospective cohort study - Chanadda Wuttikul; Noppaket Singkham; Chadathorn Hongsudta; Jindarat Danpan; Chontawan Wannagon; Wuttikrai Chaimipak; Prakaikaew Jaiwanglok; Puttasorn Detmon; Sirayut Phattanasobhon (British Journal of Clinical Pharmacology, 2026)
Aims This study aimed to determine the prevalence and patterns of potential drug–drug interactions (pDDIs), identify associated factors among people living with HIV (PLWH) with comorbidities and examine associations with clinical outcomes. Methods This multicentre retrospective study was conducted across three healthcare tiers in Thailand during 2023–2024. pDDIs were identified using Lexicomp (categories A–X). Multivariable logistic regression identified factors associated with pDDIs and assessed associations with viral suppression (viral load